1998
DOI: 10.1139/y98-049
|View full text |Cite
|
Sign up to set email alerts
|

The gut as a potential trigger of exercise-induced inflammatory responses

Abstract: Multiple lines of evidence support the hypothesis that ischemia-induced impairment of normal gut barrier function, with loss of the normal tonic counterinflammatory influence of the gut immune system, contributes to the expression of uncontrolled inflammation in critically ill victims of trauma and overwhelming infection. The clinical syndrome known as the systemic inflammatory response syndrome (SIRS), which embodies uncontrolled inflammation in trauma and sepsis, is reproduced in its entirety by vigourous ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 33 publications
2
31
0
2
Order By: Relevance
“…Endotoxaemia due to increased intestinal barrier permeability during strenuous exercise has been recognised in human athletes and Thoroughbred racehorses [35,36]. The potential for bacterial translocation from the gastrointestinal tract during exercise has also been proposed [37]. Gram-positive cocci, consistent with the synovial isolates from the present study, were occasionally identified in a study of bacteraemia in horses with diarrhoea [29].…”
Section: Origins Of Bacteraemiasupporting
confidence: 67%
“…Endotoxaemia due to increased intestinal barrier permeability during strenuous exercise has been recognised in human athletes and Thoroughbred racehorses [35,36]. The potential for bacterial translocation from the gastrointestinal tract during exercise has also been proposed [37]. Gram-positive cocci, consistent with the synovial isolates from the present study, were occasionally identified in a study of bacteraemia in horses with diarrhoea [29].…”
Section: Origins Of Bacteraemiasupporting
confidence: 67%
“…The gut has long being regarded as a ‘trigger’ or ‘promoter’ of sepsis and multiorgan failure (MOF); the important role of gut dysfunction has been illustrated in numerous studies [24-27]. Marshall aptly described the gastrointestinal tract as an ‘undrained abscess’ [28].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike psychosocial stress, exercise is accompanied by target tissue metabolic signals (e.g., profound change in pH, lactic acid, temperature, PO 2 , and PCO 2 ) that themselves can independently alter immune mediators [like heat shock proteins (38,73)] and leukocyte function (76). There is even evidence that exercise may be accompanied by translocation of gut bacteria into the central circulation, causing a classic antigen-mediated systemic immune response (18,58,85). Finally, in recent years, Pedersen, Febbraio, and their collaborators have made the groundbreaking discovery that working muscle tissue itself produces immune mediators like IL-6 and IL-8 (2,37).…”
Section: The Stress and Inflammatory Response To Exercisementioning
confidence: 99%